Gamma irradiated thermoluminescence response of Ge-doped SiO 2 fibre - Wahib, N.; Zulkepely, N.N.; Mat Nawi, S.N.; Amin, Y.M.; Ling, Y.S.; Abdul Sani, S.F.; Maah, M.J.; Bradley, D.A. (Elsevier, 2015)
Over the past decade and more, considerable interest has been shown in the thermoluminescence (TL) properties of silica-based single-mode optical fibres, in particular investigating potential ionising radiation dosimetry applications. Herein, study has been made of TL glow curve, dose response, reproducibility and fading of 6. mol% Ge-doped silica, fabricated in-house and produced in the form of cylindrical fibres. Three different pairings of doped-core and silica cladding diameters were produced: (40, 241). μm, (80, 483). μm and (100, 604). μm. The TL results were compared against that of TLD-100, one of the most sensitive commercially available LiF-based TL media. For all three pairings of diameters, closely similar TL glow curve were obtained, formed of a single peaked structure with a maximum TL yield located between the temperatures 250 and 310. °C. The TL yield of the fibres were linear over the range of doses investigated, from 1. Gy up to 10. Gy, their dose response exceeding that of TLD-100, the samples also being found to be reusable, without evidence of degradation.